Analyzing Public School Education Inequalities in the Dallas-Fort Worth Metroplex - Duvvuri, Saawan S. (Eximia, 2024)
Purpose: This paper investigates the influences of racial and socioeconomic factors on public schools' performance in the Dallas-Fort Worth (DFW) Metroplex. Research Methods: I obtained data from the Texas Education Agency (TEA) and the American Community Survey (ACS), representing 366,568 students attending 239 public high schools in the DFW Metroplex, which included public schools located in Colin County, Dallas County, Tarrant County, and Denton County. I measured public school performance based on graduation rate metrics and average SAT scores from graduating students. Findings: I found a significant correlation between racial and socioeconomic factors on public school performance. I found that the percent composition of socioeconomically disadvantaged students was the highest correlator to decreased academic performance. Further, I found a positive correlation between the percentage of socioeconomically disadvantaged students attending a given high school in relation to the percentage of African-American and Hispanic students attending a given high school. Notably, I found that public schools in the DFW Metroplex were highly segregated by racial and socioeconomic factors. Implications: This study highlights the necessity for policy pushes to diversify public school districts. Many public schools in the DFW Metroplex remain extensively segregated by racial and socioeconomic factors, and our findings underscore the importance of ensuring equitable resource distribution amongst public schools, specifically in school systems with large percentages of African-American, Hispanic, and socioeconomically disadvantaged students.